Pelatihan Digital Leadership Untuk Aparatur Desa Dalam Mewujudkan Smart Village - Gunawan, Ahmad; Rohmatul Manan, Irma; Sucipto, Imam; Heri Kusumah, Dadang; Wahyu Wirjawan, Tri; Suer Darmanto, Ucok (Jurnal Pelita Pengabdian, 2025)
The development of digital technology offers significant opportunities for villages to optimize human resource potential in realizing the smart village concept. The implementation of digital technology at the village level is expected to improve public service quality, enhance governance transparency, and foster sustainable development innovation. However, in practice, limited digital literacy and insufficient leadership capacity among village officials remain major challenges. Village officials require digital leadership skills that not only focus on technological mastery but also encompass strategic vision, change management, and data-driven resource management. This community service program was designed to enhance the digital leadership capacity of village officials through a series of structured training activities. The implementation method consisted of three main stages: (1) a needs assessment survey to map digital literacy levels and identify challenges, (2) face-to-face training sessions focusing on digital leadership concepts, technology management, and strategies for digital-based public service delivery, and (3) post-training online mentoring to ensure sustainable implementation. The results indicate a significant improvement in understanding digital leadership concepts, skills in utilizing technology for village governance, and the emergence of creative initiatives from participants to develop digital-based village services. This training is expected to serve as an initial step toward building villages that are adaptive to digital transformation, equipped with competitive officials, and capable of managing change effectively. The sustainability of this program is crucial to strengthening the foundation for establishing independent and innovative smart villages.